2020
DOI: 10.1111/aphw.12227
|View full text |Cite
|
Sign up to set email alerts
|

Is Passive Sport Engagement Positively Associated with Happiness?

Abstract: Background Previous empirical evidence has shown the positive relationship between happiness or subjective well‐being (SWB) and sport participation. Nevertheless, passive sport participation has traditionally been ignored as a correlate with happiness. Methods Based on a sample of 1,632 Spanish people, one ordered probit model and three extended ordered probit models with an ordinal endogenous covariate technique and robust standard errors were applied. Results We find that different forms of passive sport par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Passive sport involvement has a stronger association with individual happiness than active sport participation, according to LeraLópez et al [ 51 ], underlining the significance of specific forms of sport engagement as a source of relational benefits. The current study broadens the field's understanding of athletic participation and pleasure, emphasizing the relevance of passive involvement and social connections in explaining this association.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Passive sport involvement has a stronger association with individual happiness than active sport participation, according to LeraLópez et al [ 51 ], underlining the significance of specific forms of sport engagement as a source of relational benefits. The current study broadens the field's understanding of athletic participation and pleasure, emphasizing the relevance of passive involvement and social connections in explaining this association.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These methods usually consist of a single-item (i.e., "All things considered, in general, how happy would you say you are?") to measure happiness in the LTPA domain [23][24][25][26][27][28]. This item has been validated [29,30] and tested for its temporal stability (test-retest reliability; r = 0.86; [31]).…”
Section: Happinessmentioning
confidence: 99%
“…That is, previous literature suggests direct sports participation, known as active sports engagement, is linked to reduced mental distress and better mental health [e.g., ( 10 )]. However, there is growing literature on passive sports engagement (e.g., attendance at live sporting events, LSEs; watching sports on TV), which has been associated with greater happiness than active sports engagement ( 13 ). Research has shown that sports spectatorship is associated with increased SWB across all ages at racket sports events ( 14 ), associated with both short-term and long-term SWB in college students ( 15 ), and associated with life satisfaction ( 16 ) and happiness ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the above literature suggests LSE attendance offers potential improvement of SWB, it suffers from several gaps. Firstly, the existing research lacks generalizability by focusing narrowly on: (a) specific sports [e.g., baseball; ( 31 ); racket sports; ( 14 )], (b) single dimensions of SWB [e.g., life satisfaction; ( 16 ); happiness; ( 13 , 32 )], and (c) subgroups in the population [e.g., college students; ( 15 ); older adults; ( 20 )]. Secondly, this literature predominantly explores the relationship between LSE attendance and SWB, and, to the authors' best knowledge, there is little research on the association between LSE attendance and loneliness .…”
Section: Introductionmentioning
confidence: 99%